Paiements pour services environnementaux en Indonésie : incitations économiques ou motivations sociales ? - Renaud Lapeyre; Romain Pirard; Beria Leimona (Développement Durable et Territoires)
Analyzing a Payment for Environmental Services (PES) scheme in Indonesia, this article questions the alleged effectiveness of economic incentives to change land use decisions. According to the standard PES theory of change, farmers respond to payments and change their land use decisions accordingly. However, at the project level impacts depend on how the signal is transmitted and understood. Results from an extensive household survey indicate that farmers join the scheme for intrinsic motivations rather than because of economic incentives; and farmer group leaders display disproportionate power of decision while individual farmers have limited understanding of the PES. Hence, land use patterns might not depend on the economic incentive only; rather they are determined by the local social and cultural context. This in turn qualifies the strong (yet contested) economic assumptions that underlie the emergence of PES schemes and their modus operandi in developing countries.